2007
DOI: 10.1016/j.shpsb.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Propensities and probabilities

Abstract: Popper's introduction of ''propensity'' was intended to provide a solid conceptual foundation for objective single-case probabilities. By considering the partly opposed contributions of Humphreys and Miller and Salmon, it is argued that when properly understood, propensities can in fact be understood as objective single-case causal probabilities of transitions between concrete events. The chief claim is that propensities are well-explicated by describing how they fit into the existing formal theory of branchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…8 Haybron briefly notes this possibility, but seems to think that is at best an unusual practice (Haybron 2008, p. 34). 9 The notion of a propensity has proved extremely difficult to define precisely (see Belnap 2007 for an overview). For present purposes it should suffice to notice that while not identical to probabilities of outcomes, propensities are closely similar to such probabilities, and are regularly used to explain probabilities and ground predictions about the frequency of events.…”
Section: The Case For the Dispositional Viewmentioning
confidence: 99%
“…8 Haybron briefly notes this possibility, but seems to think that is at best an unusual practice (Haybron 2008, p. 34). 9 The notion of a propensity has proved extremely difficult to define precisely (see Belnap 2007 for an overview). For present purposes it should suffice to notice that while not identical to probabilities of outcomes, propensities are closely similar to such probabilities, and are regularly used to explain probabilities and ground predictions about the frequency of events.…”
Section: The Case For the Dispositional Viewmentioning
confidence: 99%
“…Christopher Hitchcock suggested that there is a significant task for the propensity theorist to explain why some axiomatisation of probability holds of this new physical property. 47 There are also other attempts to address Humphreys' paradox, such as Albert (2007) and Belnap (2007), which for lack of space we cannot discuss here.…”
Section: The Challengementioning
confidence: 99%
“…− For an application of BST to the semantics of counterfactuals, see Placek and Müller (2007). − Objective single case probabilities based on BST are developed in Weiner and Belnap (2006), Müller (2005), and Belnap (2007b). A rather preliminary application in quantum information theory is sketched in Müller (2007); for an analysis of Bell's theorem, see Placek (2010).…”
Section: Branching Space-times (Bst)mentioning
confidence: 99%